Approaches and discussions about the museum space, heritage and communication in the comparative study between Museum and Miracle Hall of the Bomfim Sanctuary in Salvador, Bahia (Cadernos de Sociomuseologia, 2017)
The research carried out had as objective to analyze how the ex-votive practices, present in the Sanctuary of the Bomfim, are linked to the popular culture of the payers of promise that are inherent to the social classes that transit freely through the room of miracles, and the ex-votive objects that Are museograted at the Museum of Ex-votos. It was noted the need to interpret and elucidate the new cultural dimensions and meanings of art and popular religiosity by addressing the conceptual followings of the terms that surround and represent the history and formation of the Sanctuary of the Lord of Bomfim, such as the sacro and the Profane, aesthetics, folkcommunication and museology that are cross-cutting themes that, at the end of the studies, we perceive to be intrinsically linked. Thus elucidating the understanding, as it gives its contextualization with the environments worked and the different forms of communication, which is propitiated in the spaces covered in the research.Keyword: ex-votos, hall of miracles, Museum of Ex-votos, patrimonialization, communication, Sanctuary of the Lord of Bomfim.